Relevant issues of testing quality of drugs in the form of tablets - E. L. Kovaleva; O. A. Matveeva; E. E. Kolganova; M. M. Mironova (Регуляторные исследования и экспертиза лекарственных средств)
The article reviews major ways of streamlining approaches to testing the following quality parameters of drugs presented in the dosage form oftablets: “Identification”, “Dissolution”, “Disintegration”, “Related impurities”, “Residual organic solvents”, “Assay”. The article describes results of a comparative analysis of requirements laid down in the leading world pharmacopoeias, WHO documents and national requirements for tablets standardization. The analysis covers such issues as classification of drugs, terms used to describe various tablet groups, differences in the choice of test methods, as well as in approaches to assessment of parameters and use of reference standards. The analysis makes it possible to define national requirements for tablets quality, which is particularly important in view of the future work on the development of pharmacopoeial monographs on drugs for the State Pharmacopoeia of the Russian Federation.